Disclosure on Sustainability Reports, Foreign Board, Foreign Ownership, Indonesia Sustainability Reporting Awards and Firm Value - Ismul Aksan; Evi Gantyowati (Journal of Accounting and Strategic Finance, 2020)
This study aims to investigate how disclosure on sustainability reports, foreign on boards, and foreign ownership affect firm value. Indonesia Sustainability Reporting Award (ISRA) is used to moderate the impact of the disclosure on the sustainability report on the firm value from 2013 to 2017. This study uses 37 firms as a sample with 159 observations and using panel data analysis. Subgroup analysis is used to test the existence or absence of homologizer moderation. The result showed that only the disclosure of sustainability has a positive impact on firm value. Foreign board and foreign ownership have been shown to not affect firm value. Additional testing is performed by splitting types of companies that have become state-owned enterprises (SOEs) and non-SOE, as well as kinds of services & finance and Manufacturing & others. We found that foreign commissioners in the service and finance sectors category have a positive effect on firm value, and foreign ownership in State-Owned Enterprises (SOEs) has a positive influence on firm value. Therefore, it is suggested that the organization of ISRA should disclose their winning criteria since it can be used as information in decision-making